Emotional Intelligence and its relation to leadership skills of School Principals in Bethlehem Governorate - Ghboun, Rula Yousef; Abu Khayran, Ashraf Mohammad; Shuibat, Mohammad Awad (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying emotional intelligence and its relationship to leadership skills of schools’ principals in Bethlehem Governorate. The population of the study consisted of all (179) school principals of Bethlehem Governorate. The study was conducted in academic year 2018/2019. The researchers used a stratified random sample of (140) members which represents 78.5% of the study population. To achieve the objectives of the study, the researchers used the emotional intelligence test (Global Emotional) (40) questions. The researchers also developed a leadership skills questionnaire. The questionnaire consisted of (32) items distributed over four domains. Validity and reliability of the tools were verified using appropriate statistical methods. The results of the study showed that the degree of emotional intelligence of the schools’ principals in Bethlehem governorate from their own point of view came moderate. It was also found that the degree of leadership skills among schools’ principals in Bethlehem governorate came high. There was a significant moderate degree of correlation between the level of emotional intelligence and the leadership skills of the schools’ principals in Bethlehem governorate from their own point of view, as well as to the fields. That is, the higher the level of emotional intelligence, the greater the degree of leadership skills of schools’ principals in the Bethlehem Governorate from their own point of view.